Automatic analysis of subthreshold operation in CMOS digital circuits - Cavalaria, Hugo Alexandre Nunes (2018)
The Internet of Things (IoT) paradigm is enabling easy access and interaction with a wide variety of devices, some of them self-powered, equipped with microcontrollers, sensors and sensor networks. Low power and ultra-low-power strategies, as never before, have a huge importance in today’s CMOS integrated circuits, as all portable devices quest for the never-ending battery life, but also with smaller and smaller dimensions every day. The solution is to use clever power management strategies and reduce drastically power consumption in IoT chips. Dynamic Voltage and Frequency Scaling techniques can be rewardingly, and using operation at subthreshold power-supply voltages can effectively achieve significant power savings. However, reducing power-supply voltages impose reduction of performance and, consequently, delay increase, in turn it makes the circuit more vulnerable to operational-induced delay-faults and transientfaults. What is the best compromise between power, delay and performance? This thesis proposes an automatic methodology and tool to perform power-delay analysis in CMOS gates and circuits, to identify automatically the best compromise between power and delay. By instantiating SPICE simulator, the proposed tool can automatically perform analysis such as: power-delay product, energy-delay product, power dissipation, or even dynamic and static power dissipations. The optimum operation point in respect to the power-supply voltage is defined, for each circuit or sub-circuit and considering subthreshold operation or not, to the minimum power-supply voltage where the delays do not increase too much and that implements a compromise between delay and power consumption. The algorithm is presented, along with CMOS circuit examples, all the analysis’ results are shown for typical benchmark circuits. Results indicate that subthreshold voltages can be a good compromise in reducing power and increasing delays.